Nature and types of sociological theory - "Martindale, Don" (Boston, 1960)
The Nature and Types of Sociological Theory is one of the most important and systematic source-books on sociological theory. ... By exploring the nature, grounds, and explanatory powers of the various forms of sociological theory, the author has rendered a valuable service for the students of social sciences.
Keywords: Sociology